UNDERSTANDING THE BEHAVIOR OF PONOROGO COMMUNITY IN RECEIVING COVID-19 VACCINATION: A HEALTH BELIEF MODEL PERSPECTIVE - Sari, Eka Permata; Purwanti, Lina Ema; Nasriati, Ririn (Indonesian Journal of Health Science, 2025)
Community behavior in accepting the COVID-19 vaccination still contains a lot of controversy. Negative news causes differences in the community's perception and response to behavior. This study aims to analyze the perception and behavior of the community in receiving the COVID-19 vaccination with the health model theory approach. The design of this study is cross-sectional, with the population of the Banaran Village, Pulung District, Ponorogo Regency, a total of 2,220 people. The number of respondents in this study was 100 people chosen by purposive sampling techniques. Research instruments using a questionnaire. In addition, data were analyzed using the Chi-Squared test. The results showed the relationship between the perception and behavior of the people receiving the COVID-19 vaccination, with a value of 0,000 <0.05. Increasing public perception and behaviors, the importance of COVID-19 vaccination can be applied using the theory of health belief models. The role of health workers is vital in educating the public about the significance of COVID-19 vaccination in suppressing transmission, severity, to death from COVID-19.